Terahertz Scanless Hypertemporal Imaging - Zanotto, Luca; Balistreri, Giacomo; Rovere, Andrea; Kwon, O. Pil; Morandotti, Roberto; Piccoli, Riccardo; Razzari, Luca (Laser and Photonics Reviews, 2023)
Since its first demonstration in 1995, terahertz time-domain imaging has attracted an increasingly growing interest for its ability to reveal spectral fingerprints of materials and probe changes in refractive index and absorption, as well as detect the inner structure of complex objects via time-of-flight measurements. Practically, however, its widespread use has been hampered by the very long acquisition time typically required to spatially raster-scan the object, and for each spatial point, record the field in time via a delay line. Here, this fundamental bottleneck is addressed by implementing a scanless single-pixel imaging scheme, which sets the path for an unprecedented reduction of both system complexity and acquisition time. By properly exploiting natural wave diffraction, time-to-space encoding applied to terahertz point detection allows for an almost instantaneous capture of the terahertz waveforms, while multidimensional images are reconstructed via a computational approach. The scheme is a promising solution for the development of next-generation fast and compact terahertz imagers perfectly suitable for high-repetition-rate laser sources.
Keywords: Acquisition time; Complex objects; Compressed-Sensing; Inner structure; Scanless; Scanless acquisition; Spectral fingerprints; Tera Hertz; Terahertz multidimensional imaging; Time-domain imaging; compressed sensing; scanless acquisition; terahertz multidimensional imaging